Clear cell chondrosarcoma of the hyoid bone: a case report - Kitajima, Tatsuya; Takimoto, Masafumi; Shimane, Toshikazu; Enomoto, Tatsuhito; Ohara, Jun; Yamochi, Toshiko; Otani, Yurie; Fukushima, Hirofumi; Ota, Hirotaka (JOURNAL OF JAPAN SOCIETY FOR HEAD AND NECK SURGERY, 2025)
Clear cell chondrosarcoma （CCCS） is a rare, low-grade chondroplastic bone tumor classified as a distinct subtype of chondrosarcoma. CCCS rarely occurs in the head and neck region. This report presents a case of CCCS involving the hyoid bone, along with a literature review. A 77-year-old Japanese woman presented with a left cervical mass. Imaging via computed tomography and magnetic resonance imaging identified a primary tumor in the hyoid bone. Puncture aspiration cytology indicated a Class Ⅲ diagnosis, raising suspicion of malignancy. The tumor, along with the surrounding connective tissue and adjacent hyoid muscles on the cephalocaudal side of the tumor, were excised. Histopathological analysis revealed clear cells with abundant cytoplasm, either clear or slightly acidophilic. Immunohistochemistry showed S-100 positivity, with cytokeratin （CK） 7, CK18, and CK AE1/AE3 negative. Periodic acid-Schiff-positive granules were also observed in the cytoplasm. Based on these findings, a diagnosis of CCCS was established, with clear resection margins. Long-term follow-up is essential, as CCCS often recurs locally or metastasizes distantly after 5 years.